MAHASISWA DAN HUBUNGAN ANTARAGAMA (KAJIAN ATAS SIMPUL IMAN COMMUNITY YOGYAKARTA) - Diki Ahmad (UIN Sunan Kalijaga Yogyakarta, 2020)
This article discusses Simpul Iman Community Yogyakarta as an organization formed from the results of dialogue. Simpul Iman Community Yogyakarta is a student organization with different religious university backgrounds that is UIN Sunan Kalijaga as a representation of Islam, UKDW as a representation of Christianity, and USD as a representation of Catholicism. This organization was born in response to the rise of violence in the name of religion and the number of students involved in it. This organization was formed as a forum for cooperation between students of different religions with scientific backgrounds in the religious studies and theology who would later become agents of change in the future. Therefore, as an organization formed from the results of dialogue, how the implementation of cooperation is realized in social life, and how the influence of Simpul Iman Community on social change.